2020
DOI: 10.3390/ma13143177
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental and Numerical Research for Plastic Working of Nickel Matrix Composite Coatings

Abstract: In the machine, metallurgical, and shipbuilding industries, steel products with alloy and composite coatings based on nickel may be used. It is expedient to improve the physicochemical properties of the surface layer of products as they have a significant roughness value after thermal spraying. It is therefore important to finish the layers applied by flame spraying, where machining is used for this purpose. However, it causes a loss of coating material, which is quite expensive. Therefore, in order to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Ni-Al alloy and Ni-Al-Al 2 O 3 composite coatings, obtained by flame spraying, were investigated. The samples with shafts shape of steel C45 (ArcelorMittal, D ąbrowa Górnicza, Poland) (C-0.45%, Cr-0.4%, Mo-0.1%, Mn-0.7%, Si-0.3%, Ni-0.4%, P-0.045%, S-0.045%) [26] and spraying coatings were researched. The flame sprayed coatings were characterized by appreciable value of surface roughness.…”
Section: Methodsmentioning
confidence: 99%
“…Ni-Al alloy and Ni-Al-Al 2 O 3 composite coatings, obtained by flame spraying, were investigated. The samples with shafts shape of steel C45 (ArcelorMittal, D ąbrowa Górnicza, Poland) (C-0.45%, Cr-0.4%, Mo-0.1%, Mn-0.7%, Si-0.3%, Ni-0.4%, P-0.045%, S-0.045%) [26] and spraying coatings were researched. The flame sprayed coatings were characterized by appreciable value of surface roughness.…”
Section: Methodsmentioning
confidence: 99%
“…Burnishing is one of the methods of finishing metals and their alloys, sinters and plastics, which involves the use of local plastic deformation [1][2][3], generated in the surface layer of the object [4][5][6][7][8][9], as a result of specific (force and kinematic) interaction of hard and a smooth tool (in the shape of a ball, disc, roller or other) with a machined surface [10][11][12][13][14][15][16][17][18]. The surface state and quality after previous treatment significantly depend on its quality after previous treatment [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In paper [4], the structure of the surface after burnishing and turning was analyzed, taking into account roughness parameters, as well as the photographs of the specimen surface and the bearing area curve. The steel products with alloy and composite coatings based on nickel with numerical and experimental tests of the plastic processing of alloy coatings were carried out in [5] and showed that after burnishing, the roughness was reduced to 1/12 and the alloy coatings were strengthened by 25%. Skoczylas et al [6,7] report the results of experimental studies on the impact of ball burnishing parameters on the roughness, microstructure and microhardness of the surface layer of laser-cut C45 steel parts.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary assumptions made before the tests assumed that the introduced asymmetry of the circumferential rate of the work rolls would make it possible to obtain both a product with the desirable geometry and favorable mechanical properties of bimetallic materials. Depending on the type of material and deformation parameters, the effects of deformation strengthening can be removed by dynamic or static healing and (static, dynamic, and metadynamic) recrystallization [ 25 , 26 , 27 ]. During the rolling process, the phenomenon of dynamic recrystallization or dynamic recovery occurs during deformation [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another problem with the uneven distribution of the deformation into the layers is the bending of the bimetallic band after it comes out of the rolling gap [ 11 , 18 , 20 ]. One of the methods of increasing the evenness of deformation of bimetallic sheet metals and obtaining a simple sheet metal is to introduce asymmetry of the peripheral speed of the work rolls (i.e., kinetic asymmetry) [ 17 , 25 , 30 ].…”
Section: Introductionmentioning
confidence: 99%